국내산 밀 전분 및 종실 경도 특성이 생면 품질에 미치는 영향 - 박진희(Jin Hee Park); 박철수(Chul Soo Park); 강천식(Chon-Sik Kang); 양진우(Jinwoo Yang); 정한용(Han-Yong Jung); 김경민(Kyeong-Min Kim); 최창현(Chang-Hyun Choi); 손재한(Jae-Han Son); 손지영(Jiyoung Son); 박태일(Tae-Il Park); 김경훈(Kyeong-Hoon Kim) (Korean journal of breeding, 2021)
This study was conducted to investigate the effect of starch properties on the texture of cooked noodles from Korean wheat. Thegenetic composition of GBSS I (granule bound starch synthase I, called waxy protein) and puroindoline, which affect the amylose contentand kernel hardness, was also evaluated. Waxy wheats carrying Wx-1 null alleles showed clearly different starch properties, high swellingpower, pasting viscosity, breakdown and paste clarity, unsuitable texture of cooked noodles, and low hardness and springiness. Two partialwaxy soft wheats carrying single or double null alleles at the Wx-1 locus gene, and Pina-D1a and Pinb-D1a alleles exhibited a softer andhigher elasticity texture of the cooked noodles than Korean wheats carrying wild-type Wx-1 null alleles. There were no significant differencesin the starch properties and texture of cooked noodles according to the puroindoline composition. A principal component analysis showeda strong negative relationship between the amylose content and starch swelling power, and these traits also improved the springiness andcohesiveness of the cooked noodles prepared from non-waxy Korean wheat. Joongmo2012, a double null partial waxy wheat, showed higherstarch swelling power and springiness of the cooked noodles than other non-waxy Korean wheats. KCI Citation Count: 6